Improving patient positioning and posture for breast cancer radiotherapy using DIBH and SGRT techniques by modifying fixation devices and tightening SGRT tolerances - Järvinen, Lauri; Laaksomaa, Marko; Björkqvist, Mikko; Keyriläinen, Jani (VM Media Group sp. z o.o, 2026)
Background: Surface guided radiotherapy (SGRT) aids to place the patient in the correct position before radiotherapy. The aim of this retrospective observational study was to investigate how modifying patient fixation devices and tightening SGRT tolerances reduces residual errors and interfractional positioning variability in patients’ position and posture for deep inspiration breath hold radiotherapy (RT) of breast cancer.
Materials and methods: The patient fixation devices were changed by introducing a 10° wedge-shaped foam cushion under the patients’ back and rotating the previously used knee wedge to support the pelvic position more tightly. Additionally, the SGRT tolerance values were tightened from 8 or 12 mm to 5 mm. Patient Group A (n = 25) had had breast-conserving surgery and Group B (n = 25) mastectomy before RT. Residual errors of bony landmarks, breast outline and indicators of patient posture were retrospectively analyzed in a treatment planning system from 472 and 467 fractions before, and from 571 and 665 fractions after modifications for Groups A and B, respectively.
Results: Statistically significant improvements (p < 0.05) in residual errors were found at the positions of the shoulder joint, T1 and T2 vertebrae (Group B), and the sternum (Groups A and B), as well as the rib cage (Group B) and the breast outline (Group A) in kV images. Systematic error for patient pitch decreased from 3.7 mm to 2.0 mm (Group A) and from 3.2 mm to 1.8 mm (Group B) (p < 0.05).
Conclusions: The modifications improved patients’ position and pitch.